Supporting ecosystem for farmers' food traceability participation: A systematic review - Airong Zhang; Christina Maxwell; Francesco Tacconi; Alyce Lythall; David Smith; Xinlong Guan (Journal of Agriculture and Food Research)
Food traceability from ‘farm to fork’ enhances supply chain transparency and ensures food safety, quality, and authenticity. Farmers play a pivotal role in enabling traceability by digitally recording production processes and input data and sharing this information with supply chain partners. However, despite the benefits, the adoption of digital traceability systems among farmers remains low due to various challenges. A clear understanding of the supporting ecosystem is essential to facilitate their participation. This paper aims to identify the facilitators and barriers influencing farmers' engagement in digital traceability systems, based on a systematic review of existing literature. Following PRISMA guidelines, 39 records were identified across the agricultural industry and synthesised into five themes using qualitative content analysis: value and culture, technology, data, capability, and data sharing. These themes were then used to create a Digital Maturity Framework for Traceability Implementation (DMFTI) which offers a holistic and structured perspective on the ecosystem needed to support farmers in adopting digital traceability. The DMFTI is intended to serve as a practical tool for the agricultural industry and policymakers to design targeted strategies that promote effective traceability implementation among farmers.